2020
DOI: 10.1155/2020/6853652
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of a Peptide Containing Novel Oral Spray on Streptococcus mutans

Abstract: Objective. To investigate the antibacterial effect of a novel antimicrobial peptide containing oral spray GERM CLEAN on Streptococcus mutans (S. mutans) in vitro and further explore the related mechanisms at phenotypic and transcriptional levels. Methods. The disk diffusion method was used to preliminarily appraise the antimicrobial effect of GERM CLEAN. The minimal inhibitory concentration (MIC) of GREM CLEAN towards S. mutans was determined by the broth dilution method. S. mutans virulence-related phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 115 publications
1
10
0
Order By: Relevance
“…The gyra A gene studied is also an important virulent gene of S. mutans. The DNA gyrase encoding gyra A is a housekeeping gene offers protection to S.mutans against antibiotics and environmental stress [ 38 , 39 ]. In the present study, the synthesized GA-AgNPs inhibited the virulence of gyra Agene.…”
Section: Resultsmentioning
confidence: 99%
“…The gyra A gene studied is also an important virulent gene of S. mutans. The DNA gyrase encoding gyra A is a housekeeping gene offers protection to S.mutans against antibiotics and environmental stress [ 38 , 39 ]. In the present study, the synthesized GA-AgNPs inhibited the virulence of gyra Agene.…”
Section: Resultsmentioning
confidence: 99%
“…mutans is 100% mass fraction and 1/2 MIC GERM CLEAN decreased EPS production, biofilm formation, acidogenicity, and related gene expression of S. mutans (Xiong et al, 2020). In this study, we further analyzed the effects of GERM CLEAN with same concentration on S. mutans and C. albicans dual-species biofilm and evaluated whether it affected the bovine enamel demineralization.…”
Section: Discussionmentioning
confidence: 99%
“…The suspension of each microorganism was diluted to OD 600nm = 0.5 with YNBB for the subsequent assays. In our previous study, we have found that the MIC of GERM CLEAN on S. mutans was 100% mass fraction (stock solution) and that GERM CLEAN of its 1/2 MIC (50% mass fraction) showed antibacterial effect on S. mutans in vitro (Xiong et al., 2020). In this study, we aimed to further evaluate the effect of GERM CLEAN with the same mass fraction on dual‐species microorganisms of S. mutans and C. albicans in vitro.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Global Burden of Disease Study 2016 revealed that caries of permanent teeth had the greatest prevalence, decayed permanent, and deciduous teeth ranked in second and fifth place, respectively, in highest incidence diseases [ 2 ]. Streptococcus mutans ( S. mutans ), a major extracellular polymeric substances producer, is the most well-known biofilm forming bacteria in oral cavity and was reported as most associated microbe in the transition of oral flora from a healthy one to a cariogenic one [ 3 ]. It has been proven that decrease or eradication of S. mutans can diminish or prevent caries development [ 4 ].…”
Section: Introductionmentioning
confidence: 99%